A review of Food Security and Human Nutrition Issues in Nepal. - Shively, Gerald.; Gars, Jared; Sununtnasuk, Celeste. (Tufts University. Tisch Library., 2016)
Nepal faces multiple development challenges, including chronic and widespread food insecurity and adult and child malnutrition. This paper represents a brief review of topics and available evidence regarding food security, malnutrition, and related subjects in Nepal. It is intended to document important source material and provide an overview of topics for non-specialists or those moving into new areas of concern.; Nutrition School: Technical Reports.; Keywords: Technical Report, Nepal, malnutrition, food insecurity, source material.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy